Risk Attitude and Nonmarital Birth - Uwe Jirjahn; Cornelia Struewing (Institute for the Study of Labor (IZA), 2016)
Using data of adult women from the German Socio-Economic Panel (SOEP), we find that risk tolerance is associated with a higher probability of an out-of-partnership birth. In contrast, we find no association between risk tolerance and the probability of a cohabiting birth.
Keywords: D10; J12; J13; 330; risk attitude; out-of-partnership birth; cohabiting birth